1989
DOI: 10.1007/bf02327256
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict the zinc status of soils for maize

Abstract: The objective of this study, carried out over 2 years, was to evaluate the effect of soil properties on the response of maize (Zea mays L.) to zinc applications and relate these properties to soil test Zn for predicting the Zn status of soils considering the effect of environmental conditions. The relative yield, expressed as an index of crop response, was related through multiple regression to CEC (or clay), electrical conductivity (or exchangeable Na), and bulk density consistently throughout the two year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Using the Cate-Nelson method, by Zare et al (2009) A. H. Khoshgoftarmansh et al Zn by DTPA and EDTA for corn in non-saline soils in central Iran, were 1.5 and 1.17 mg kg −1 , respectively. In earlier studies critical levels of about 0.6, has been reported for corn (Srivastava and Gupta, 1996;Pal et al, 1989). Takkar et al (1989) reported that the critical level of soil Zn for maize ranged from 0.38 to 1.40 mg kg −1 .…”
Section: Determination Of the Critical Level In Soil By Cate-nelson Mmentioning
confidence: 91%
See 1 more Smart Citation
“…Using the Cate-Nelson method, by Zare et al (2009) A. H. Khoshgoftarmansh et al Zn by DTPA and EDTA for corn in non-saline soils in central Iran, were 1.5 and 1.17 mg kg −1 , respectively. In earlier studies critical levels of about 0.6, has been reported for corn (Srivastava and Gupta, 1996;Pal et al, 1989). Takkar et al (1989) reported that the critical level of soil Zn for maize ranged from 0.38 to 1.40 mg kg −1 .…”
Section: Determination Of the Critical Level In Soil By Cate-nelson Mmentioning
confidence: 91%
“…On alkaline soils, 0.6 mg-kg −1 DTPA-extractable Zn is considered to be critical for corn (Bansal et al, 1990a(Bansal et al, , 1990b. The critical concentration of soil Zn for corn was 0.6 mg kg −1 for some soils of India (Pal et al, 1989;Srivastava and Gupta, 1996). Singh (1986) reported the DTPA-extractable soil Zn and plant tissue Zn critical level for corn as 0.54 and 15.4 mg kg −1 , respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Inappropriately managed irrigated soils can also become saline due to the accumulation of salts. In Madhya Pradesh, India, critical EC values of 35 mS cm -1 , where DTPA-Zn is below 0.6 mg Zn kg -1 and 55 mS cm -1 where the DTPA-Zn is above 1.0 mg Zn kg -1 and/or the soil has a loam or sandy clay loam texture, are used in a model for predicting the risk of Zn deficiency in maize (Pal et al 1989).…”
Section: Saline Soilsmentioning
confidence: 99%
“…The deficiency of Zn has been frequently referred to maize, which is a crop very sensitive to it (Murphy and Walsh, 1983;Pal et al, 1989). In general this deficiency is not caused by the total concentrations in the soil of this element but by very low concentrations in the soil solution (Adriano, 1986).…”
Section: Introductionmentioning
confidence: 99%